Time course for acquiring toileting independence in patients with subacute stroke: a prospective cohort study - Shin Kitamura; Yohei Otaka; Shintaro Uehara; Yudai Murayama; Kazuki Ushizawa; Yuya Narita; Naho Nakatsukasa; Daisuke Matsuura; Rieko Osu; Kunitsugu Kondo; Sachiko Sakata (Journal of Rehabilitation Medicine)
Objective: To determine the time course of longitudinal changes in the independence level of toileting-related subtasks in post-stroke patients.